A kind of high wear-resistant and corrosion-resistant mechanical steel and preparation method thereof

By setting a base layer, metal layer and coating layer on the surface of the mechanical steel substrate, using copper powder, nickel powder, chromium powder, molybdenum powder, titanium dioxide @ graphene/carbon nanotube/ceramic whisker composite materials and modified epoxy resins, the problem of insufficient wear and corrosion resistance of traditional mechanical steel materials is solved, and high wear and corrosion resistance is achieved.

CN119307851BActive Publication Date: 2025-03-04ZHUHAI LONGSHENG MOULD MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411834084.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-04
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

Traditional mechanical steel materials are difficult to maintain long-term wear and corrosion resistance in complex and changing working environments, resulting in shortening of equipment life and increasing maintenance costs.

Method used

The base layer, metal layer and coating layer are arranged in sequence on the surface of the pretreated mechanical steel substrate. The base layer is composed of copper powder, nickel powder, chromium powder and molybdenum powder. The metal layer uses titanium dioxide @ graphene/carbon nanotube/ceramic whisker composite material, and a layer of titanium dioxide is deposited on its surface. The coating layer is composed of modified epoxy resin and modified carbon black.

Benefits of technology

It realizes high wear resistance and corrosion resistance of mechanical steel, extends the service life of the equipment, and reduces maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of protective coatings for metal materials, specifically a highly wear-resistant and corrosion-resistant mechanical steel and a preparation method thereof. The present invention comprises the following steps: S1: pre-treating the surface of a mechanical steel substrate to obtain pre-treated mechanical steel; S2: sequentially setting a primer layer and a metal layer on the surface of the pre-treated mechanical steel: S21: spraying primer layer powder on the surface of the pre-treated mechanical steel using supersonic flame spraying technology to obtain a primer layer; S22: spraying metal layer powder on the surface of the primer layer using supersonic flame spraying technology to obtain a metal layer; S3: uniformly brushing an enhanced coating onto the surface of the metal layer, drying and curing to obtain a coating layer; and preparing highly wear-resistant and corrosion-resistant mechanical steel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal material protective coatings, in particular to a highly wear-resistant and corrosion-resistant mechanical steel and a preparation method thereof. Background Art

[0002] With the rapid development of modern industry, mechanical equipment is facing increasingly severe challenges in wear resistance and corrosion resistance in complex and changing working environments. Traditional mechanical steel materials are often difficult to maintain stable performance over a long period of time, resulting in shortened equipment life and increased maintenance costs.

[0003] Therefore, it is particularly important to develop a mechanical steel material with both high wear resistance and corrosion resistance. This high wear and corrosion resistant mechanical steel can adapt to various extreme working environments, thereby ensuring the long-term stable operation of mechanical equipment. Summary of the invention

[0004] The object of the present invention is to provide a highly wear-resistant and corrosion-resistant mechanical steel and a preparation method thereof, so as to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A highly wear-resistant and corrosion-resistant mechanical steel is obtained by sequentially arranging a primer layer, a metal layer, and a coating layer on the surface of a pretreated mechanical steel substrate;

[0007] The thickness of the base layer is 0.1mm~0.3mm;

[0008] The thickness of the metal layer is ≥0.5 mm;

[0009] The thickness of the coating layer is 3 μm to 5 μm.

[0010] Furthermore, the method for preparing the highly wear-resistant and corrosion-resistant mechanical steel comprises the following steps:

[0011] S1: pre-treating the surface of the mechanical steel substrate to be sprayed to obtain pre-treated mechanical steel;

[0012] S2: Set the primer layer and metal layer in sequence on the pre-treated mechanical steel surface:

[0013] S21: The primer powder is sprayed on the surface of the pre-treated mechanical steel by using the supersonic flame spraying technology to obtain the primer;

[0014] S22: using supersonic flame spraying technology to spray metal layer powder onto the surface of the base layer to obtain a metal layer;

[0015] S3: Brush the reinforcing coating evenly onto the surface of the metal layer, and wait for it to dry and solidify to obtain a coating layer; and prepare highly wear-resistant and corrosion-resistant mechanical steel.

[0016] Furthermore, the pretreatment includes two steps of cleaning and sandblasting.

[0017] The cleaning process is as follows: using degreased acetone, anhydrous ethanol and deionized water to ultrasonically clean the surface of the mechanical steel in sequence to remove the oil stains on the surface, completing the cleaning, and drying for standby use.

[0018] The process parameters of the sandblasting roughening are: the grinding sand is any one of quartz sand, brown corundum sand, and ceramic sand, and its particle size is 0.6mm~2mm; the compressed air pressure is 0.4MPa~0.5MPa; the sandblasting distance is 100mm~120mm; and the sandblasting angle is 72°~78°.

[0019] Furthermore, the surface roughness of the pretreated mechanical steel is Ra=7.0~9.0.

[0020] After mechanical steel leaves the factory, dirt such as oil will remain on its surface, which is not conducive to the subsequent coating processing in this plan. Therefore, it needs to be cleaned to remove the oil on its surface. In order to strengthen the bonding between the coating and the mechanical steel substrate, the mechanical steel is pre-treated by sandblasting roughening in the plan. By controlling the process parameters of sandblasting roughening, the most suitable surface roughness for processing is obtained.

[0021] Furthermore, the base coating powder is obtained by mixing and ball milling the following components: by mass percentage, 80% to 89% copper powder, 5% to 10% nickel powder, 3% to 5% chromium powder, and 3% to 5% molybdenum powder.

[0022] The average particle size of the primer powder is 30 μm to 50 μm.

[0023] Furthermore, the metal layer powder is obtained by mixing, pressing, sintering and ball milling the following components: by mass percentage, 90% to 97% of the base layer powder and 3% to 10% of the titanium dioxide@graphene / carbon nanotube / ceramic whisker composite material.

[0024] The average particle size of the metal layer powder is 30 μm to 50 μm.

[0025] Furthermore, the pressure used for the compression molding is 150MPa~200MPa.

[0026] Furthermore, the sintering method is: under vacuum, heating to 350°C~450°C at a heating rate of 20°C / min~40°C / min and sintering for 1h~2h; then heating to 900°C~1100°C at a heating rate of 5°C / min~8°C / min and sintering for 0.5h~1h, waiting for the furnace to cool, taking it out, and completing the sintering.

[0027] Furthermore, the ball milling method is: adding 8wt%~10wt% of sodium carboxymethyl cellulose-ethanol solution and the raw material to be ball milled into a ball mill, ball milling to the desired particle size with a ball-to-material ratio of (10~15):1 and a ball milling speed of 350rpm~450rpm, filtering and drying to complete the ball milling; wherein the ratio between the raw material to be ball milled and the sodium carboxymethyl cellulose-ethanol solution is (3g~4g):10mL.

[0028] Furthermore, the preparation method of the titanium dioxide @ graphene / carbon nanotube / ceramic whisker composite material is as follows: (1) dispersing carboxylated carbon nanotubes in deionized water to obtain a carbon nanotube suspension; dispersing ceramic whiskers in a 1wt%~5wt% polyvinyl pyrrolidone aqueous solution to obtain a ceramic whisker suspension; dispersing graphene oxide in deionized water to obtain a graphene suspension; (2) under ultrasonic dispersion, slowly adding the carbon nanotube suspension to the ceramic whisker suspension, ultrasonically treating for 1h~3h, then adding the graphene suspension to the mixed system, continuing the ultrasonic treatment for 1h~3h, and finally adding ascorbic acid to the mixed system and ultrasonically treating for 5min ~15min later, the temperature is raised to 90℃~100℃ and kept for 1h~5h to terminate the reaction, and the graphene / carbon nanotube / ceramic whisker composite material is obtained by filtering and drying; (3) Tetrabutyl titanate, diethanolamine and anhydrous ethanol are slowly added to deionized water under stirring. After the raw materials are completely dissolved, the temperature is raised to 45℃~60℃ and stirring is continued for 1h~2h to obtain titanium dioxide sol; (4) The graphene / carbon nanotube / ceramic whisker composite material is added to the titanium dioxide sol, ultrasonically treated for 5min~15min, and then allowed to stand for 2h~6h. After filtering, drying and grinding, a titanium dioxide@graphene / carbon nanotube / ceramic whisker composite material is obtained.

[0029] Furthermore, the mass ratio of the carboxylated carbon nanotubes, ceramic whiskers, graphene oxide and ascorbic acid is (0.1-0.2):(0.01-0.05):1:1.

[0030] Furthermore, the ratio of tetrabutyl titanate, diethanolamine, anhydrous ethanol and deionized water is 5g: (0.5~2)mL: 20mL: 20mL; wherein diethanolamine mainly acts as a surfactant, which can be adsorbed onto the surface of titanium dioxide, prevent titanium dioxide from agglomerating and improve its morphology, thereby obtaining spherical titanium dioxide particles with small and uniform particle size.

[0031] Furthermore, the ceramic whiskers include but are not limited to a combination of one or more of silicon carbide whiskers, silicon nitride whiskers, and aluminum nitride whiskers.

[0032] Furthermore, the ratio of the graphene / carbon nanotube / silicon carbide whisker composite material to the titanium dioxide sol is 1 g:40 mL.

[0033] Furthermore, the process parameters of the supersonic flame spraying technology are: oxygen pressure of 1.5MPa~1.6MPa, oxygen flow rate of 1L / min~1.2L / min, propane pressure of 0.3MPa~0.5MPa, propane flow rate of 100L / min~110L / min, nitrogen powder feeding pressure of 0.5MPa~0.6MPa, and spraying distance of 180mm~200mm.

[0034] In the present invention, a layer of primer is first set on the surface of pre-treated mechanical steel. The primer has good bonding strength with both the mechanical steel and the metal layer, and exists as a bridge between the mechanical steel and the metal layer. Compared with directly setting the metal layer on the mechanical steel, it has better bonding strength; the raw material of the primer is obtained by mixing copper powder, nickel powder, chromium powder, and molybdenum powder. Copper has good bonding strength with mechanical steel. Nickel, chromium, and molybdenum are further added in the scheme to improve the bonding strength of the primer. In order to improve the corrosion resistance and wear resistance of the subsequent metal layer, the present invention combines carbon nanotubes and ceramic whiskers with graphene to obtain a graphene / carbon nanotube / ceramic whisker composite material, and deposits a layer of titanium dioxide on its surface to obtain a titanium dioxide@graphene / carbon nanotube / ceramic whisker composite material; it is designed to be used as the raw material of the metal layer and mixed with other alloy powders and sprayed on the mechanical steel to improve the wear resistance and corrosion resistance of the mechanical steel. After sintering together with alloy powder, the titanium dioxide @ graphene / carbon nanotube / ceramic whisker composite material can form an alloy material with uniform and continuous metal phase, and then through ball milling and supersonic flame spraying treatment, a dense and continuous high-quality metal layer can be obtained. Under the synergistic effect of titanium dioxide, graphene, carbon nanotubes, and ceramic whiskers, the metal layer can be endowed with excellent corrosion resistance and wear resistance, thereby achieving protection of mechanical steel. And due to the coating of titanium dioxide, the interface bonding force between the titanium dioxide @ graphene / carbon nanotube / ceramic whisker composite material and the metal phase can be effectively improved.

[0035] Furthermore, the reinforced coating includes the following components: by weight, 30 to 35 parts of modified epoxy resin, 6 to 10 parts of modified carbon black, 3 to 8 parts of corrosion inhibitor, 4 to 10 parts of film former, 3 to 8 parts of anti-aging agent, 1 to 4 parts of defoaming agent, 5 to 10 parts of curing agent, 25 to 30 parts of anhydrous ethanol, and 40 to 50 parts of deionized water.

[0036] Furthermore, the preparation method of the enhanced coating is as follows: (1) under a nitrogen atmosphere, perfluoropolyether diol and terminal hydroxyl fluorinated polyester polysiloxane are dissolved in tetrahydrofuran, and then water-based epoxy resin and catalyst are added thereto, and then the temperature is raised to 100°C~150°C and stirred for reaction for 1h~5h, and then the modified epoxy resin is obtained by vacuum distillation and cooling; (2) 5-amino-2-pyrazinoic acid is dissolved in deionized water, and then carbon black is added thereto, and then the temperature is raised to 70°C~80°C and stirred for reaction for 10min~30min, and then the modified carbon black is obtained by filtering, washing and drying; (3) the modified epoxy resin, anhydrous ethanol and deionized water are stirred and mixed, and then formic acid is added to the mixed system to adjust the pH to 5~6, and then the corrosion inhibitor and modified carbon black are added to the mixed system in sequence and stirred and mixed, and finally a film former, an anti-aging agent, a defoaming agent and a curing agent are added to the mixed system and stirred and mixed to obtain an enhanced coating.

[0037] Furthermore, the mass ratio of the perfluoropolyether diol, the terminal hydroxyl-containing fluorinated polyester polysiloxane, the waterborne epoxy resin and the catalyst is 1:1:(5-10):(0.1-0.6).

[0038] Furthermore, the catalyst includes but is not limited to any one of dibutyltin dilaurate, stannous octoate, methyltriphenylphosphonium bromide, and ethyltriphenylphosphonium bromide.

[0039] Furthermore, the mass ratio of the 5-amino-2-pyrazinoic acid to the carbon black is 1:(1-1.5); and the particle size of the carbon black is ≤100 nm.

[0040] Furthermore, the corrosion inhibitor is phytic acid.

[0041] Furthermore, the film-forming agent includes but is not limited to a combination of one or more of BYK-333, BYK-381, and BTK-346.

[0042] Furthermore, the anti-aging agent is V-480.

[0043] Furthermore, the defoaming agent includes but is not limited to any one of XWC-T118, XWC-T128, XWC-T165, and XWC-T131.

[0044] Furthermore, the curing agent includes but is not limited to one or more combinations of triethanolamine curing agent, isocyanate curing agent, and acid anhydride curing agent.

[0045] The present invention grafts perfluoropolyether diol and terminal hydroxyl fluorinated polyester polysiloxane onto waterborne epoxy resin, introduces fluorine-containing chains onto the waterborne epoxy resin, and obtains modified epoxy resin; then, 5-amino-2-pyrazinoic acid is used to improve carbon black, and carbon black contains a large number of hydroxyl groups, which can form hydrogen bonds with the carboxyl groups on 5-amino-2-pyrazinoic acid, so that 5-amino-2-pyrazinoic acid is grafted onto the surface of carbon black to obtain modified carbon black; finally, the modified epoxy resin, modified carbon black and other raw materials are stirred and mixed to obtain enhanced coating. Among them, the modified epoxy resin can play a hydrophobic role after subsequent coating, drying and curing due to the introduction of fluorine-containing chains, so as to avoid the attenuation of the relevant properties of the coating layer in a humid environment, thereby enabling the mechanical steel to be well protected even in a humid environment, thereby enhancing the corrosion resistance of the mechanical steel. The modified carbon black effectively weakens the interaction between carbon black molecules and prevents them from agglomerating, so that the modified carbon black can be evenly dispersed in the modified epoxy resin, thereby achieving the purpose of enhancing the wear resistance and corrosion resistance of the coating layer; and because the modified carbon black contains amino and pyrazine structures, the amino group can chemically bond with the epoxy group and fluorine on the modified epoxy resin to form a cross-linked network, so that the coating layer has better mechanical properties, thereby enabling the mechanical steel to obtain better wear resistance, corrosion resistance and bonding properties. The pyrazine structure can chemically adsorb and form covalent bonds with the copper atoms on the metal layer, which can enhance the bonding performance with the metal layer while also playing a certain role in corrosion inhibition. Finally, under the synergistic effect of raw materials such as modified epoxy resin and modified carbon black, a coating layer with excellent bonding performance, wear resistance and corrosion resistance is obtained, which can well protect the mechanical steel from corrosion and wear damage, and still has a significant protective effect even in a humid environment.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] 1. The present invention pre-treats the mechanical steel and then arranges a primer layer, a metal layer and a coating layer on the surface thereof. The layers are closely connected, and finally a highly wear-resistant and corrosion-resistant mechanical steel with excellent corrosion resistance and wear resistance is comprehensively prepared.

[0048] 2. The titanium dioxide @ graphene / carbon nanotube / ceramic whisker composite material prepared by the present invention is an important component of the metal layer, which can significantly enhance the wear resistance and corrosion resistance of the metal layer, thereby achieving the enhancement of mechanical steel.

[0049] 3. In the present invention, under the synergistic effect of raw materials such as modified epoxy resin and modified carbon black, a coating layer with excellent bonding performance, wear resistance and corrosion resistance is obtained. The coating layer acts as a barrier to protect the metal layer, and the coating layer can improve the corrosion resistance and wear resistance of mechanical steel to a certain extent; in addition, since the modified epoxy resin introduces fluorine chain ends, it has hydrophobicity and can effectively prevent water from entering, which can greatly weaken the damage of water to the coating layer and further avoid the damage of water to the metal layer, thereby achieving full protection of mechanical steel. DETAILED DESCRIPTION

[0050] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0051] It should be noted that the purchasers of all raw materials involved in the present invention include, without any special restrictions, illustratively:

[0052] Graphene oxide, flake diameter <40 μm, thickness <1 nm, purchased from Angxing New Carbon Materials Changzhou Co., Ltd.;

[0053] Silicon carbide whiskers, diameter <500 nm, length <12 nm, purchased from Forsman Technology (Beijing) Co., Ltd.;

[0054] Carboxylated double-walled carbon nanotubes, inner diameter 1~3nm, outer diameter 2~4nm, length 0.5~2μm, -COOH content: ≤2.6wt%, purchased from Hubei Chengfeng Chemical Co., Ltd.;

[0055] Tetrabutyl titanate with a purity of 99%, diethanolamine with a purity of 99%, and triethanolamine with a purity of 99% were purchased from Shanghai Jinjinle Industrial Co., Ltd.;

[0056] The molecular weight of perfluoropolyether diol was 2000 and it was purchased from Taipuda New Materials Co., Ltd.

[0057] The model of the hydroxy-terminated fluorinated polyester polysiloxane is IOTA 3375F, which was purchased from Anhui IOTA Silicone Oil Co., Ltd.;

[0058] Water-based epoxy resin, model: AB-EP-12, purchased from Zhejiang Anbang New Materials Development Co., Ltd.;

[0059] 5-Amino-2-pyrazinoic acid, purity 98%, was purchased from JACS-Zhengzhou Jacks Chemical Products Co., Ltd.;

[0060] Film-forming agent: model BYK-333, purchased from (Alpha) Zhengzhou Huiju Chemical Co., Ltd.;

[0061] Anti-aging agent: model V-480, purchased from Guangzhou Good New Material Technology Co., Ltd.;

[0062] Defoaming agent: Model: XWC-T118, purchased from Hefei Xinwancheng Environmental Protection Technology Co., Ltd.

[0063] Example 1: A method for preparing highly wear-resistant and corrosion-resistant mechanical steel:

[0064] S1: Pre-processing:

[0065] Cleaning: Use degreased acetone, anhydrous ethanol, and deionized water to ultrasonically clean the surface of No. 45 steel in turn to remove the oil on the surface, complete the cleaning, and dry it for later use;

[0066] Sandblasting roughening: The cleaned No. 45 steel is placed in a sandblasting machine for sandblasting roughening treatment to obtain a pre-treated No. 45 steel with a surface roughness of Ra=7.5. The process parameters are: 1.5mm brown corundum sand is used as abrasive sand, the compressed air pressure is 0.4MPa; the sandblasting distance is 100mm; the sandblasting angle is 75°;

[0067] S2: Set the base layer and metal layer:

[0068] S21: Set the base layer:

[0069] S211: Copper powder, nickel powder, chromium powder and molybdenum powder are weighed in a mass ratio of 85:8:4:3, and mixed evenly to obtain a mixed metal powder; the mixed metal powder and 10 wt % sodium carboxymethyl cellulose-ethanol solution are added into a ball mill in a ratio of 4 g:10 mL, and ball-to-material ratio is 10:1, and ball milling speed is 400 rpm, and the powder is ball-milled to an average particle size of 40 μm to obtain a base layer powder;

[0070] S212: The base layer powder was sprayed on the surface of the pre-treated 45 steel material by supersonic flame spraying technology to obtain a 0.2mm thick base layer; the working parameters of the supersonic flame spraying technology were: oxygen pressure of 1.5MPa, oxygen flow of 1.1L / min, propane pressure of 0.4MPa, propane flow of 100L / min, nitrogen powder feeding pressure of 0.6MPa, and spraying distance of 190mm;

[0071] S22: Set the metal layer:

[0072] S221: Preparation of titanium dioxide @ graphene / carbon nanotube / silicon carbide whisker composite materials: (1) Disperse carboxylated carbon nanotubes in deionized water to obtain a carbon nanotube suspension; disperse silicon carbide whiskers in a 3wt% polyvinyl pyrrolidone aqueous solution to obtain a silicon carbide whisker suspension; disperse graphene oxide in deionized water to obtain a graphene suspension; (2) Under ultrasonic dispersion, slowly add the carbon nanotube suspension to the silicon carbide whisker suspension, ultrasonically treat for 2h, then add the graphene suspension to the mixed system, continue ultrasonically treating for 2h, and finally add ascorbic acid to the mixed system. After ultrasonic treatment for 10min, heat to 95℃ and keep warm for 3h to terminate the reaction. Filter and dry to obtain graphene / carbon nanotube / carbon whisker suspension. (3) under stirring, tetrabutyl titanate, diethanolamine and anhydrous ethanol were slowly added into deionized water (the ratio of the four was 5 g: 1 mL: 20 mL: 20 mL). After the raw materials were completely dissolved, the temperature was raised to 50 °C and stirred for 1.5 h to obtain titanium dioxide sol; (4) the graphene / carbon nanotube / silicon carbide whisker composite material was added into the titanium dioxide sol (the ratio of the two was 1 g: 40 mL), ultrasonically treated for 10 min, and then allowed to stand for 4 h. After filtering, drying and grinding, titanium dioxide@graphene / carbon nanotube / silicon carbide whisker composite material was obtained;

[0073] S222: Weigh the base layer powder and titanium dioxide@graphene / carbon nanotube / silicon carbide whisker composite material in a mass ratio of 95:5, stir and mix them evenly, and then press them into shape at 200 MPa; then place them in a vacuum sintering furnace, heat them to 400°C at a heating rate of 30°C / min, and sinter them for 1.5h; then heat them to 1000°C at a heating rate of 5°C / min, and sinter them for 1h, wait for the furnace to cool, take them out, and complete the sintering;

[0074] S223: adding the sintered product and 10 wt % sodium carboxymethyl cellulose-ethanol solution in a ratio of 4 g:10 mL into a ball mill, and ball milling the mixture to an average particle size of 40 μm at a ball-to-material ratio of 10:1 and a ball milling speed of 400 rpm to obtain a metal layer powder;

[0075] S224: The metal layer powder is sprayed on the surface of the base layer by supersonic flame spraying technology to obtain a 0.5mm thick metal layer; the working parameters of the supersonic flame spraying technology are: oxygen pressure of 1.5MPa, oxygen flow of 1.1L / min, propane pressure of 0.4MPa, propane flow of 100L / min, nitrogen powder feeding pressure of 0.6MPa, and spraying distance of 190mm;

[0076] S3: Set up paint layer:

[0077] S31: Preparation of enhanced coating: (1) Under nitrogen atmosphere, perfluoropolyether diol and terminal hydroxyl fluorinated polyester polysiloxane are dissolved in an appropriate amount of tetrahydrofuran, and then water-based epoxy resin and dibutyltin dilaurate are added thereto, and then the mixture is heated to 120°C and stirred for 4 hours, and then distilled under reduced pressure and cooled to obtain a modified epoxy resin, wherein the mass ratio of perfluoropolyether diol, terminal hydroxyl fluorinated polyester polysiloxane, water-based epoxy resin and dibutyltin dilaurate is 1:1:8:0.4; (2) 5-amino-2-pyrazinoic acid is dissolved in deionized water, and then a particle size of ≤100 is added thereto. nm carbon black, and then stirring and heating to 75°C for 20 minutes, filtering, washing and drying to obtain modified carbon black, wherein the mass ratio of 5-amino-2-pyrazinoic acid to carbon black is 1:1.2; (3) stirring and mixing the modified epoxy resin, anhydrous ethanol and deionized water, and then adding formic acid to the mixed system to adjust the pH to 5.5, and then adding phytic acid and modified carbon black to the mixed system in turn and stirring and mixing, and finally adding film former BYK-333, anti-aging agent V-480, defoamer XWC-T118 and triethanolamine to the mixed system and stirring and mixing to obtain a reinforced coating;

[0078] The reinforced coating comprises the following components: by weight, 32 parts of modified epoxy resin, 8 parts of modified carbon black, 5 parts of phytic acid, 6 parts of film former BYK-333, 5 parts of anti-aging agent V-480, 3 parts of defoamer XWC-T118, 8 parts of triethanolamine, 25 parts of anhydrous ethanol, and 50 parts of deionized water.

[0079] S32: The reinforcing coating is evenly brushed onto the surface of the metal layer, and dried and cured at 120° C. to obtain a coating layer with a thickness of 4 μm; and a highly wear-resistant and corrosion-resistant No. 45 steel is prepared.

[0080] Example 2: A method for preparing highly wear-resistant and corrosion-resistant mechanical steel:

[0081] S1: Pre-processing:

[0082] Cleaning: Use degreased acetone, anhydrous ethanol, and deionized water to ultrasonically clean the surface of No. 45 steel in turn to remove the oil on the surface, complete the cleaning, and dry it for later use;

[0083] Sandblasting roughening: The cleaned No. 45 steel is placed in a sandblasting machine for sandblasting roughening treatment to obtain a pre-treated No. 45 steel with a surface roughness of Ra=7.5. The process parameters are: 1.5mm brown corundum sand is used as abrasive sand, the compressed air pressure is 0.4MPa; the sandblasting distance is 100mm; the sandblasting angle is 75°;

[0084] S2: Set the base layer and metal layer:

[0085] S21: Set the base layer:

[0086] S211: Copper powder, nickel powder, chromium powder and molybdenum powder are weighed in a mass ratio of 85:8:4:3, and mixed evenly to obtain a mixed metal powder; the mixed metal powder and 10 wt % sodium carboxymethyl cellulose-ethanol solution are added into a ball mill in a ratio of 4 g:10 mL, and ball-to-material ratio is 10:1, and ball milling speed is 400 rpm, and the powder is ball-milled to an average particle size of 40 μm to obtain a base layer powder;

[0087] S212: The base layer powder was sprayed on the surface of the pre-treated 45 steel material by supersonic flame spraying technology to obtain a 0.2mm thick base layer; the working parameters of the supersonic flame spraying technology were: oxygen pressure of 1.5MPa, oxygen flow of 1.1L / min, propane pressure of 0.4MPa, propane flow of 100L / min, nitrogen powder feeding pressure of 0.6MPa, and spraying distance of 190mm;

[0088] S22: Set the metal layer:

[0089] S221: Preparation of titanium dioxide @ graphene / carbon nanotube / silicon carbide whisker composite materials: (1) Disperse carboxylated carbon nanotubes in deionized water to obtain a carbon nanotube suspension; disperse silicon carbide whiskers in a 3wt% polyvinyl pyrrolidone aqueous solution to obtain a silicon carbide whisker suspension; disperse graphene oxide in deionized water to obtain a graphene suspension; (2) Under ultrasonic dispersion, slowly add the carbon nanotube suspension to the silicon carbide whisker suspension, and ultrasonically treat for 2h, then add the graphene suspension to the mixed system, and continue ultrasonically treating for 2h, and finally add ascorbic acid to the mixed system, ultrasonically treat for 10min, then heat to 95℃ and keep warm for 3h to terminate the reaction, filter and dry to obtain graphene / carbon nanotube / carbonized carbon whisker composite material. Silicon whisker composite material (the mass ratio of carboxylated carbon nanotubes, silicon carbide whiskers, graphene oxide, and ascorbic acid is 0.1:0.01:1:1); (3) Under stirring, tetrabutyl titanate, diethanolamine, and anhydrous ethanol are slowly added to deionized water (the ratio of the four is 5g:0.5mL:20mL:20mL). After the raw materials are completely dissolved, the temperature is raised to 50°C and stirring is continued for 1.5h to obtain titanium dioxide sol; (4) The graphene / carbon nanotube / silicon carbide whisker composite material is added to the titanium dioxide sol (the ratio of the two is 1g:40mL), ultrasonically treated for 10min, and then allowed to stand for 4h. After filtering, drying, and grinding, a titanium dioxide@graphene / carbon nanotube / silicon carbide whisker composite material is obtained;

[0090] S222: Weigh the base layer powder and titanium dioxide @ graphene / carbon nanotube / silicon carbide whisker composite material in a mass ratio of 97:3, stir and mix them evenly, and press them into shape at 200 MPa; then place them in a vacuum sintering furnace, heat them to 400°C at a heating rate of 30°C / min, and sinter them for 1.5h; then heat them to 1000°C at a heating rate of 5°C / min, and sinter them for 1h, wait for the furnace to cool, take them out, and complete the sintering;

[0091] S223: adding the sintered product and 10 wt % sodium carboxymethyl cellulose-ethanol solution in a ratio of 4 g:10 mL into a ball mill, and ball milling the mixture to an average particle size of 40 μm at a ball-to-material ratio of 10:1 and a ball milling speed of 400 rpm to obtain a metal layer powder;

[0092] S224: The metal layer powder is sprayed on the surface of the base layer by supersonic flame spraying technology to obtain a 0.5mm thick metal layer; the working parameters of the supersonic flame spraying technology are: oxygen pressure of 1.5MPa, oxygen flow of 1.1L / min, propane pressure of 0.4MPa, propane flow of 100L / min, nitrogen powder feeding pressure of 0.6MPa, and spraying distance of 190mm;

[0093] S3: Set up paint layer:

[0094] S31: Preparation of enhanced coating: (1) Under nitrogen atmosphere, perfluoropolyether diol and terminal hydroxyl fluorinated polyester polysiloxane are dissolved in an appropriate amount of tetrahydrofuran, and then water-based epoxy resin and dibutyltin dilaurate are added thereto, and then the temperature is raised to 120°C and stirred for reaction for 4 hours, and then vacuum distilled and cooled to obtain a modified epoxy resin, wherein the mass ratio of perfluoropolyether diol, terminal hydroxyl fluorinated polyester polysiloxane, water-based epoxy resin and dibutyltin dilaurate is 1:1:10:0.4; (2) 5-amino-2-pyrazinoic acid is dissolved in deionized water, and then a particle size of ≤10 is added thereto. 0nm carbon black, then stir and heat to 75℃ and stir to react for 20min, filter, wash and dry to obtain modified carbon black, wherein the mass ratio of 5-amino-2-pyrazinoic acid to carbon black is 1:1.5; (3) stir and mix the modified epoxy resin, anhydrous ethanol and deionized water, then add formic acid to the mixed system to adjust the pH to 5.5, continue to add phytic acid and modified carbon black to the mixed system in sequence and stir and mix, finally add film former BYK-333, anti-aging agent V-480, defoamer XWC-T118 and triethanolamine to the mixed system and stir and mix to obtain a reinforced coating;

[0095] The reinforced coating comprises the following components: by weight, 32 parts of modified epoxy resin, 8 parts of modified carbon black, 5 parts of phytic acid, 6 parts of film former BYK-333, 5 parts of anti-aging agent V-480, 3 parts of defoamer XWC-T118, 8 parts of triethanolamine, 25 parts of anhydrous ethanol, and 50 parts of deionized water.

[0096] S32: The reinforcing coating is evenly brushed onto the surface of the metal layer, and dried and cured at 120° C. to obtain a coating layer with a thickness of 4 μm; and a highly wear-resistant and corrosion-resistant No. 45 steel is prepared.

[0097] Example 3: A method for preparing highly wear-resistant and corrosion-resistant mechanical steel:

[0098] S1: Pre-processing:

[0099] Cleaning: Use degreased acetone, anhydrous ethanol, and deionized water to ultrasonically clean the surface of No. 45 steel in turn to remove the oil on the surface, complete the cleaning, and dry it for later use;

[0100] Sandblasting roughening: The cleaned No. 45 steel is placed in a sandblasting machine for sandblasting roughening treatment to obtain a pre-treated No. 45 steel with a surface roughness of Ra=7.5. The process parameters are: 1.5mm brown corundum sand is used as abrasive sand, the compressed air pressure is 0.4MPa; the sandblasting distance is 100mm; the sandblasting angle is 75°;

[0101] S2: Set the base layer and metal layer:

[0102] S21: Set the base layer:

[0103] S211: Copper powder, nickel powder, chromium powder and molybdenum powder are weighed in a mass ratio of 85:8:4:3, and mixed evenly to obtain a mixed metal powder; the mixed metal powder and 10 wt % sodium carboxymethyl cellulose-ethanol solution are added into a ball mill in a ratio of 4 g:10 mL, and ball-to-material ratio is 10:1, and ball milling speed is 400 rpm, and the powder is ball-milled to an average particle size of 40 μm to obtain a base layer powder;

[0104] S212: The base layer powder was sprayed on the surface of the pre-treated 45 steel material by supersonic flame spraying technology to obtain a 0.2mm thick base layer; the working parameters of the supersonic flame spraying technology were: oxygen pressure of 1.5MPa, oxygen flow of 1.1L / min, propane pressure of 0.4MPa, propane flow of 100L / min, nitrogen powder feeding pressure of 0.6MPa, and spraying distance of 190mm;

[0105] S22: Set the metal layer:

[0106] S221: Preparation of titanium dioxide @ graphene / carbon nanotube / silicon carbide whisker composite materials: (1) Disperse carboxylated carbon nanotubes in deionized water to obtain a carbon nanotube suspension; disperse silicon carbide whiskers in a 3wt% polyvinyl pyrrolidone aqueous solution to obtain a silicon carbide whisker suspension; disperse graphene oxide in deionized water to obtain a graphene suspension; (2) Under ultrasonic dispersion, slowly add the carbon nanotube suspension to the silicon carbide whisker suspension, ultrasonically treat for 2h, then add the graphene suspension to the mixed system, continue ultrasonically treating for 2h, and finally add ascorbic acid to the mixed system. After ultrasonic treatment for 10min, heat to 95℃ and keep warm for 3h to terminate the reaction. Filter and dry to obtain graphene / carbon nanotube / carbon whisker suspension. (3) under stirring, tetrabutyl titanate, diethanolamine and anhydrous ethanol were slowly added into deionized water (the ratio of the four was 5 g: 2 mL: 20 mL: 20 mL). After the raw materials were completely dissolved, the temperature was raised to 50 °C and stirred for 1.5 h to obtain titanium dioxide sol; (4) the graphene / carbon nanotube / silicon carbide whisker composite material was added into the titanium dioxide sol (the ratio of the two was 1 g: 40 mL), ultrasonically treated for 10 min, and then allowed to stand for 4 h. After filtering, drying and grinding, titanium dioxide@graphene / carbon nanotube / silicon carbide whisker composite material was obtained;

[0107] S222: Weigh the base layer powder and titanium dioxide @ graphene / carbon nanotube / silicon carbide whisker composite material in a mass ratio of 90:10, stir and mix them evenly, and press them into shape at 200 MPa; then place them in a vacuum sintering furnace, heat them to 400°C at a heating rate of 30°C / min, and sinter them for 1.5h; then heat them to 1000°C at a heating rate of 5°C / min, and sinter them for 1h, wait for the furnace to cool, take them out, and complete the sintering;

[0108] S223: adding the sintered product and 10 wt % sodium carboxymethyl cellulose-ethanol solution in a ratio of 4 g:10 mL into a ball mill, and ball milling the mixture to an average particle size of 40 μm at a ball-to-material ratio of 10:1 and a ball milling speed of 400 rpm to obtain a metal layer powder;

[0109] S224: The metal layer powder is sprayed on the surface of the base layer by supersonic flame spraying technology to obtain a 0.5mm thick metal layer; the working parameters of the supersonic flame spraying technology are: oxygen pressure of 1.5MPa, oxygen flow of 1.1L / min, propane pressure of 0.4MPa, propane flow of 100L / min, nitrogen powder feeding pressure of 0.6MPa, and spraying distance of 190mm;

[0110] S3: Set up paint layer:

[0111] S31: Preparation of enhanced coating: (1) Under nitrogen atmosphere, perfluoropolyether diol and terminal hydroxyl fluorinated polyester polysiloxane are dissolved in an appropriate amount of tetrahydrofuran, and then water-based epoxy resin and dibutyltin dilaurate are added thereto, and then the temperature is raised to 120°C and stirred for reaction for 4 hours, and then vacuum distilled and cooled to obtain a modified epoxy resin, wherein the mass ratio of perfluoropolyether diol, terminal hydroxyl fluorinated polyester polysiloxane, water-based epoxy resin and dibutyltin dilaurate is 1:1:5:0.6; (2) 5-amino-2-pyrazinoic acid is dissolved in deionized water, and then a particle size of ≤10 is added thereto. 0nm carbon black, then stir and heat to 75℃ and stir to react for 20min, filter, wash and dry to obtain modified carbon black, wherein the mass ratio of 5-amino-2-pyrazinoic acid to carbon black is 1:1; (3) stir and mix the modified epoxy resin, anhydrous ethanol and deionized water, then add formic acid to the mixed system to adjust the pH to 5.5, continue to add phytic acid and modified carbon black to the mixed system in sequence and stir and mix, finally add film former BYK-333, anti-aging agent V-480, defoamer XWC-T118 and triethanolamine to the mixed system and stir and mix to obtain a reinforced coating;

[0112] The reinforced coating comprises the following components: by weight, 32 parts of modified epoxy resin, 8 parts of modified carbon black, 5 parts of phytic acid, 6 parts of film former BYK-333, 5 parts of anti-aging agent V-480, 3 parts of defoamer XWC-T118, 8 parts of triethanolamine, 25 parts of anhydrous ethanol, and 50 parts of deionized water.

[0113] S32: The reinforcing coating is evenly brushed onto the surface of the metal layer, and dried and cured at 120° C. to obtain a coating layer with a thickness of 4 μm; and a highly wear-resistant and corrosion-resistant No. 45 steel is prepared.

[0114] Based on Example 1, a control experiment is carried out, and comparative examples 1 to 6 are set as follows:

[0115] Comparative Example 1: Comparative Example 1 is based on Example 1, with the following adjustments: no metal layer is provided, and other processes remain unchanged, specifically:

[0116] A method for preparing highly wear-resistant and corrosion-resistant mechanical steel:

[0117] S1: Pre-processing:

[0118] Cleaning: Use degreased acetone, anhydrous ethanol, and deionized water to ultrasonically clean the surface of No. 45 steel in turn to remove the oil on the surface, complete the cleaning, and dry it for later use;

[0119] Sandblasting roughening: The cleaned No. 45 steel is placed in a sandblasting machine for sandblasting roughening treatment to obtain a pre-treated No. 45 steel with a surface roughness of Ra=7.5. The process parameters are: 1.5mm brown corundum sand is used as abrasive sand, the compressed air pressure is 0.4MPa; the sandblasting distance is 100mm; the sandblasting angle is 75°;

[0120] S2: Set the bottom layer:

[0121] S21: Copper powder, nickel powder, chromium powder and molybdenum powder are weighed in a mass ratio of 85:8:4:3, and mixed evenly to obtain a mixed metal powder; the mixed metal powder and 10wt% sodium carboxymethyl cellulose-ethanol solution are added into a ball mill in a ratio of 4g:10mL, and ball-milled to an average powder particle size of 40μm at a ball-to-material ratio of 10:1 and a ball milling speed of 400rpm to obtain a base layer powder;

[0122] S22: The base layer powder was sprayed on the surface of the pre-treated 45 steel material by supersonic flame spraying technology to obtain a 0.5mm thick base layer; the working parameters of the supersonic flame spraying technology were: oxygen pressure of 1.5MPa, oxygen flow of 1.1L / min, propane pressure of 0.4MPa, propane flow of 100L / min, nitrogen powder feeding pressure of 0.6MPa, and spraying distance of 190mm;

[0123] S3: Set up paint layer:

[0124] S31: Preparation of enhanced coating: (1) Under nitrogen atmosphere, perfluoropolyether diol and terminal hydroxyl fluorinated polyester polysiloxane are dissolved in an appropriate amount of tetrahydrofuran, and then water-based epoxy resin and dibutyltin dilaurate are added thereto, and then the mixture is heated to 120°C and stirred for 4 hours, and then distilled under reduced pressure and cooled to obtain a modified epoxy resin, wherein the mass ratio of perfluoropolyether diol, terminal hydroxyl fluorinated polyester polysiloxane, water-based epoxy resin and dibutyltin dilaurate is 1:1:8:0.4; (2) 5-amino-2-pyrazinoic acid is dissolved in deionized water, and then a particle size of ≤100 is added thereto. nm carbon black, and then stirring and heating to 75°C for 20 minutes, filtering, washing and drying to obtain modified carbon black, wherein the mass ratio of 5-amino-2-pyrazinoic acid to carbon black is 1:1.2; (3) stirring and mixing the modified epoxy resin, anhydrous ethanol and deionized water, and then adding formic acid to the mixed system to adjust the pH to 5.5, and then adding phytic acid and modified carbon black to the mixed system in turn and stirring and mixing, and finally adding film former BYK-333, anti-aging agent V-480, defoamer XWC-T118 and triethanolamine to the mixed system and stirring and mixing to obtain a reinforced coating;

[0125] The reinforced coating comprises the following components: by weight, 32 parts of modified epoxy resin, 8 parts of modified carbon black, 5 parts of phytic acid, 6 parts of film former BYK-333, 5 parts of anti-aging agent V-480, 3 parts of defoamer XWC-T118, 8 parts of triethanolamine, 25 parts of anhydrous ethanol, and 50 parts of deionized water.

[0126] S32: The reinforcing coating is evenly brushed onto the surface of the base layer, and dried and cured at 120° C. to obtain a coating layer with a thickness of 4 μm; and a highly wear-resistant and corrosion-resistant No. 45 steel is prepared.

[0127] Comparative Example 2: Comparative Example 2 is based on Example 1, with the following modifications: no titanium dioxide is used to coat the graphene / carbon nanotube / silicon carbide whisker composite material, and other processes remain unchanged, specifically:

[0128] A method for preparing highly wear-resistant and corrosion-resistant mechanical steel:

[0129] S1: Pre-processing:

[0130] Cleaning: Use degreased acetone, anhydrous ethanol, and deionized water to ultrasonically clean the surface of No. 45 steel in turn to remove the oil on the surface, complete the cleaning, and dry it for later use;

[0131] Sandblasting roughening: The cleaned No. 45 steel is placed in a sandblasting machine for sandblasting roughening treatment to obtain pre-treated No. 45 steel with a surface roughness of Ra=7.5. The process parameters are: 1.5mm particle size brown corundum sand is used as grinding sand, the compressed air pressure is 0.4MPa; the sandblasting distance is 100mm; the sandblasting angle is 75°.

[0132] S2: Set the base layer and metal layer:

[0133] S21: Set the base layer:

[0134] S211: Copper powder, nickel powder, chromium powder and molybdenum powder are weighed in a mass ratio of 85:8:4:3, and mixed evenly to obtain a mixed metal powder; the mixed metal powder and 10 wt % sodium carboxymethyl cellulose-ethanol solution are added into a ball mill in a ratio of 4 g:10 mL, and ball-to-material ratio is 10:1, and ball milling speed is 400 rpm, and the powder is ball-milled to an average particle size of 40 μm to obtain a base layer powder;

[0135] S212: The base layer powder was sprayed on the surface of the pre-treated 45 steel material by supersonic flame spraying technology to obtain a 0.2mm thick base layer; the working parameters of the supersonic flame spraying technology were: oxygen pressure of 1.5MPa, oxygen flow of 1.1L / min, propane pressure of 0.4MPa, propane flow of 100L / min, nitrogen powder feeding pressure of 0.6MPa, and spraying distance of 190mm;

[0136] S22: Set the metal layer:

[0137] S221: Preparation of graphene / carbon nanotube / silicon carbide whisker composite material: (1) dispersing carboxylated carbon nanotubes in deionized water to obtain carbon nanotube suspension; dispersing silicon carbide whiskers in a 3wt% polyvinyl pyrrolidone aqueous solution to obtain silicon carbide whisker suspension; dispersing graphene oxide in deionized water to obtain graphene suspension; (2) slowly adding the carbon nanotube suspension to the silicon carbide whisker suspension under ultrasonic dispersion, ultrasonically treating for 2h, then adding the graphene suspension to the mixed system, and continuing the ultrasonic treatment for 2h, finally adding ascorbic acid to the mixed system, ultrasonically treating for 10min, heating to 95℃ and keeping warm for 3h, terminating the reaction, filtering and drying to obtain graphene / carbon nanotube / silicon carbide whisker composite material (the mass ratio of carboxylated carbon nanotubes, silicon carbide whiskers, graphene oxide and ascorbic acid is 0.15:0.03:1:1);

[0138] S222: Weigh the base layer powder and the graphene / carbon nanotube / silicon carbide whisker composite material in a mass ratio of 95:5, stir and mix them evenly, and then press them into shape at 200 MPa; then place them in a vacuum sintering furnace, heat them to 400° C. at a heating rate of 30° C. / min, and sinter them for 1.5 h; then heat them to 1000° C. at a heating rate of 5° C. / min, and sinter them for 1 h, wait for the furnace to cool, take them out, and complete the sintering;

[0139] S223: adding the sintered product and 10 wt % sodium carboxymethyl cellulose-ethanol solution in a ratio of 4 g:10 mL into a ball mill, and ball milling the mixture to an average particle size of 40 μm at a ball-to-material ratio of 10:1 and a ball milling speed of 400 rpm to obtain a metal layer powder;

[0140] S224: The metal layer powder is sprayed on the surface of the base layer by supersonic flame spraying technology to obtain a 0.5mm thick metal layer; the working parameters of the supersonic flame spraying technology are: oxygen pressure of 1.5MPa, oxygen flow of 1.1L / min, propane pressure of 0.4MPa, propane flow of 100L / min, nitrogen powder feeding pressure of 0.6MPa, and spraying distance of 190mm;

[0141] S3: Set up paint layer:

[0142] S31: Preparation of enhanced coating: (1) Under nitrogen atmosphere, perfluoropolyether diol and terminal hydroxyl fluorinated polyester polysiloxane are dissolved in an appropriate amount of tetrahydrofuran, and then water-based epoxy resin and dibutyltin dilaurate are added thereto, and then the mixture is heated to 120°C and stirred for 4 hours, and then distilled under reduced pressure and cooled to obtain a modified epoxy resin, wherein the mass ratio of perfluoropolyether diol, terminal hydroxyl fluorinated polyester polysiloxane, water-based epoxy resin and dibutyltin dilaurate is 1:1:8:0.4; (2) 5-amino-2-pyrazinoic acid is dissolved in deionized water, and then a particle size of ≤100 is added thereto. nm carbon black, and then stirring and heating to 75°C for 20 minutes, filtering, washing and drying to obtain modified carbon black, wherein the mass ratio of 5-amino-2-pyrazinoic acid to carbon black is 1:1.2; (3) stirring and mixing the modified epoxy resin, anhydrous ethanol and deionized water, and then adding formic acid to the mixed system to adjust the pH to 5.5, and then adding phytic acid and modified carbon black to the mixed system in turn and stirring and mixing, and finally adding film former BYK-333, anti-aging agent V-480, defoamer XWC-T118 and triethanolamine to the mixed system and stirring and mixing to obtain a reinforced coating;

[0143] The reinforced coating comprises the following components: by weight, 32 parts of modified epoxy resin, 8 parts of modified carbon black, 5 parts of phytic acid, 6 parts of film former BYK-333, 5 parts of anti-aging agent V-480, 3 parts of defoamer XWC-T118, 8 parts of triethanolamine, 25 parts of anhydrous ethanol, and 50 parts of deionized water.

[0144] S32: The reinforcing coating is evenly brushed onto the surface of the metal layer, and dried and cured at 120° C. to obtain a coating layer with a thickness of 4 μm; and a highly wear-resistant and corrosion-resistant No. 45 steel is prepared.

[0145] Comparative Example 3: Comparative Example 3 is based on Example 1, with the following adjustments: no modification of the waterborne epoxy resin is performed, and other processes remain unchanged, specifically:

[0146] A method for preparing highly wear-resistant and corrosion-resistant mechanical steel:

[0147] S1: Pre-processing:

[0148] Cleaning: Use degreased acetone, anhydrous ethanol, and deionized water to ultrasonically clean the surface of No. 45 steel in turn to remove the oil on the surface, complete the cleaning, and dry it for later use;

[0149] Sandblasting roughening: The cleaned No. 45 steel is placed in a sandblasting machine for sandblasting roughening treatment to obtain pre-treated No. 45 steel with a surface roughness of Ra=7.5. The process parameters are: 1.5mm particle size brown corundum sand is used as grinding sand, the compressed air pressure is 0.4MPa; the sandblasting distance is 100mm; the sandblasting angle is 75°.

[0150] S2: Set the base layer and metal layer:

[0151] S21: Set the base layer:

[0152] S211: Copper powder, nickel powder, chromium powder and molybdenum powder are weighed in a mass ratio of 85:8:4:3, and mixed evenly to obtain a mixed metal powder; the mixed metal powder and 10 wt % sodium carboxymethyl cellulose-ethanol solution are added into a ball mill in a ratio of 4 g:10 mL, and ball-to-material ratio is 10:1, and ball milling speed is 400 rpm, and the powder is ball-milled to an average particle size of 40 μm to obtain a base layer powder;

[0153] S212: The base layer powder was sprayed on the surface of the pre-treated 45 steel material by supersonic flame spraying technology to obtain a 0.2mm thick base layer; the working parameters of the supersonic flame spraying technology were: oxygen pressure of 1.5MPa, oxygen flow of 1.1L / min, propane pressure of 0.4MPa, propane flow of 100L / min, nitrogen powder feeding pressure of 0.6MPa, and spraying distance of 190mm;

[0154] S22: Set the metal layer:

[0155] S221: Preparation of titanium dioxide @ graphene / carbon nanotube / silicon carbide whisker composite materials: (1) Disperse carboxylated carbon nanotubes in deionized water to obtain a carbon nanotube suspension; disperse silicon carbide whiskers in a 3wt% polyvinyl pyrrolidone aqueous solution to obtain a silicon carbide whisker suspension; disperse graphene oxide in deionized water to obtain a graphene suspension; (2) Under ultrasonic dispersion, slowly add the carbon nanotube suspension to the silicon carbide whisker suspension, ultrasonically treat for 2h, then add the graphene suspension to the mixed system, continue ultrasonically treating for 2h, and finally add ascorbic acid to the mixed system. After ultrasonic treatment for 10min, heat to 95℃ and keep warm for 3h to terminate the reaction. Filter and dry to obtain graphene / carbon nanotube / carbon whisker suspension. (3) under stirring, tetrabutyl titanate, diethanolamine and anhydrous ethanol were slowly added into deionized water (the ratio of the four was 5 g: 1 mL: 20 mL: 20 mL). After the raw materials were completely dissolved, the temperature was raised to 50 °C and stirred for 1.5 h to obtain titanium dioxide sol; (4) the graphene / carbon nanotube / silicon carbide whisker composite material was added into the titanium dioxide sol (the ratio of the two was 1 g: 40 mL), ultrasonically treated for 10 min, and then allowed to stand for 4 h. After filtering, drying and grinding, titanium dioxide@graphene / carbon nanotube / silicon carbide whisker composite material was obtained;

[0156] S222: Weigh the base layer powder and titanium dioxide@graphene / carbon nanotube / silicon carbide whisker composite material in a mass ratio of 95:5, stir and mix them evenly, and then press them into shape at 200 MPa; then place them in a vacuum sintering furnace, heat them to 400°C at a heating rate of 30°C / min, and sinter them for 1.5h; then heat them to 1000°C at a heating rate of 5°C / min, and sinter them for 1h, wait for the furnace to cool, take them out, and complete the sintering;

[0157] S223: adding the sintered product and 10 wt % sodium carboxymethyl cellulose-ethanol solution in a ratio of 4 g:10 mL into a ball mill, and ball milling the mixture to an average particle size of 40 μm at a ball-to-material ratio of 10:1 and a ball milling speed of 400 rpm to obtain a metal layer powder;

[0158] S224: The metal layer powder is sprayed on the surface of the base layer by supersonic flame spraying technology to obtain a 0.5mm thick metal layer; the working parameters of the supersonic flame spraying technology are: oxygen pressure of 1.5MPa, oxygen flow of 1.1L / min, propane pressure of 0.4MPa, propane flow of 100L / min, nitrogen powder feeding pressure of 0.6MPa, and spraying distance of 190mm;

[0159] S3: Set up paint layer:

[0160] S31: Preparation of enhanced coating: (1) Dissolve 5-amino-2-pyrazinoic acid in deionized water, then add carbon black with a particle size of ≤100 nm, stir and heat to 75°C for 20 min, filter, wash and dry to obtain modified carbon black, wherein the mass ratio of 5-amino-2-pyrazinoic acid to carbon black is 1:1.2; (2) Stir and mix water-based epoxy resin, anhydrous ethanol and deionized water, then add formic acid to the mixed system to adjust the pH to 5.5, continue to add phytic acid and modified carbon black to the mixed system in turn and stir and mix, finally add film former BYK-333, anti-aging agent V-480, defoamer XWC-T118 and triethanolamine to the mixed system and stir and mix to obtain enhanced coating;

[0161] The reinforced coating comprises the following components: by weight, 32 parts of waterborne epoxy resin, 8 parts of modified carbon black, 5 parts of phytic acid, 6 parts of film former BYK-333, 5 parts of anti-aging agent V-480, 3 parts of defoamer XWC-T118, 8 parts of triethanolamine, 25 parts of anhydrous ethanol, and 50 parts of deionized water.

[0162] S32: The reinforcing coating is evenly brushed onto the surface of the metal layer, and dried and cured at 120° C. to obtain a coating layer with a thickness of 4 μm; and a highly wear-resistant and corrosion-resistant No. 45 steel is prepared.

[0163] Comparative Example 4: Comparative Example 4 is based on Example 1, with the following adjustments: no modification treatment is performed on the carbon black, and other processes remain unchanged, specifically:

[0164] A method for preparing highly wear-resistant and corrosion-resistant mechanical steel:

[0165] S1: Pre-processing:

[0166] Cleaning: Use degreased acetone, anhydrous ethanol, and deionized water to ultrasonically clean the surface of No. 45 steel in turn to remove the oil on the surface, complete the cleaning, and dry it for later use;

[0167] Sandblasting roughening: The cleaned No. 45 steel is placed in a sandblasting machine for sandblasting roughening treatment to obtain pre-treated No. 45 steel with a surface roughness of Ra=7.5. The process parameters are: 1.5mm particle size brown corundum sand is used as grinding sand, the compressed air pressure is 0.4MPa; the sandblasting distance is 100mm; the sandblasting angle is 75°.

[0168] S2: Set the base layer and metal layer:

[0169] S21: Set the base layer:

[0170] S211: Copper powder, nickel powder, chromium powder and molybdenum powder are weighed in a mass ratio of 85:8:4:3, and mixed evenly to obtain a mixed metal powder; the mixed metal powder and 10 wt % sodium carboxymethyl cellulose-ethanol solution are added into a ball mill in a ratio of 4 g:10 mL, and ball-to-material ratio is 10:1, and ball milling speed is 400 rpm, and the powder is ball-milled to an average particle size of 40 μm to obtain a base layer powder;

[0171] S212: The base layer powder was sprayed on the surface of the pre-treated 45 steel material by supersonic flame spraying technology to obtain a 0.2mm thick base layer; the working parameters of the supersonic flame spraying technology were: oxygen pressure of 1.5MPa, oxygen flow of 1.1L / min, propane pressure of 0.4MPa, propane flow of 100L / min, nitrogen powder feeding pressure of 0.6MPa, and spraying distance of 190mm;

[0172] S22: Set the metal layer:

[0173] S221: Preparation of titanium dioxide @ graphene / carbon nanotube / silicon carbide whisker composite materials: (1) Disperse carboxylated carbon nanotubes in deionized water to obtain a carbon nanotube suspension; disperse silicon carbide whiskers in a 3wt% polyvinyl pyrrolidone aqueous solution to obtain a silicon carbide whisker suspension; disperse graphene oxide in deionized water to obtain a graphene suspension; (2) Under ultrasonic dispersion, slowly add the carbon nanotube suspension to the silicon carbide whisker suspension, ultrasonically treat for 2h, then add the graphene suspension to the mixed system, continue ultrasonically treating for 2h, and finally add ascorbic acid to the mixed system. After ultrasonic treatment for 10min, heat to 95℃ and keep warm for 3h to terminate the reaction. Filter and dry to obtain graphene / carbon nanotube / carbon whisker suspension. (3) under stirring, tetrabutyl titanate, diethanolamine and anhydrous ethanol were slowly added into deionized water (the ratio of the four was 5 g: 1 mL: 20 mL: 20 mL). After the raw materials were completely dissolved, the temperature was raised to 50 °C and stirred for 1.5 h to obtain titanium dioxide sol; (4) the graphene / carbon nanotube / silicon carbide whisker composite material was added into the titanium dioxide sol (the ratio of the two was 1 g: 40 mL), ultrasonically treated for 10 min, and then allowed to stand for 4 h. After filtering, drying and grinding, titanium dioxide@graphene / carbon nanotube / silicon carbide whisker composite material was obtained;

[0174] S222: Weigh the base layer powder and titanium dioxide@graphene / carbon nanotube / silicon carbide whisker composite material in a mass ratio of 95:5, stir and mix them evenly, and then press them into shape at 200 MPa; then place them in a vacuum sintering furnace, heat them to 400°C at a heating rate of 30°C / min, and sinter them for 1.5h; then heat them to 1000°C at a heating rate of 5°C / min, and sinter them for 1h, wait for the furnace to cool, take them out, and complete the sintering;

[0175] S223: adding the sintered product and 10 wt % sodium carboxymethyl cellulose-ethanol solution in a ratio of 4 g:10 mL into a ball mill, and ball milling the mixture to an average particle size of 40 μm at a ball-to-material ratio of 10:1 and a ball milling speed of 400 rpm to obtain a metal layer powder;

[0176] S224: The metal layer powder is sprayed on the surface of the base layer by supersonic flame spraying technology to obtain a 0.5mm thick metal layer; the working parameters of the supersonic flame spraying technology are: oxygen pressure of 1.5MPa, oxygen flow of 1.1L / min, propane pressure of 0.4MPa, propane flow of 100L / min, nitrogen powder feeding pressure of 0.6MPa, and spraying distance of 190mm;

[0177] S3: Set up paint layer:

[0178] S31: Preparation of enhanced coating: (1) Under nitrogen atmosphere, perfluoropolyether diol and terminal hydroxyl fluorinated polyester polysiloxane are dissolved in an appropriate amount of tetrahydrofuran, and then water-based epoxy resin and dibutyltin dilaurate are added thereto, and then the mixture is heated to 120°C and stirred for reaction for 4 hours, and then distilled under reduced pressure and cooled to obtain a modified epoxy resin, wherein the mass ratio of perfluoropolyether diol, terminal hydroxyl fluorinated polyester polysiloxane, water-based epoxy resin and dibutyltin dilaurate is 1:1:8:0.4; (2) The modified epoxy resin, anhydrous ethanol and deionized water are stirred and mixed, and then formic acid is added to the mixed system to adjust the pH to 5.5, and phytic acid and carbon black are added to the mixed system in sequence and stirred and mixed, and finally, a film former BYK-333, an anti-aging agent V-480, a defoaming agent XWC-T118 and triethanolamine are added to the mixed system and stirred and mixed to obtain an enhanced coating;

[0179] The reinforced coating comprises the following components: by weight, 32 parts of modified epoxy resin, 8 parts of carbon black, 5 parts of phytic acid, 6 parts of film former BYK-333, 5 parts of anti-aging agent V-480, 3 parts of defoamer XWC-T118, 8 parts of triethanolamine, 25 parts of anhydrous ethanol, and 50 parts of deionized water.

[0180] S32: The reinforcing coating is evenly brushed onto the surface of the metal layer, and dried and cured at 120° C. to obtain a coating layer with a thickness of 4 μm; and a highly wear-resistant and corrosion-resistant No. 45 steel is prepared.

[0181] Comparative Example 5: Comparative Example 5 is based on Example 1, with the following adjustments: no coating layer is provided, and other processes remain unchanged, specifically:

[0182] A method for preparing highly wear-resistant and corrosion-resistant mechanical steel:

[0183] S1: Pre-processing:

[0184] Cleaning: Use degreased acetone, anhydrous ethanol, and deionized water to ultrasonically clean the surface of No. 45 steel in turn to remove the oil on the surface, complete the cleaning, and dry it for later use;

[0185] Sandblasting roughening: The cleaned No. 45 steel is placed in a sandblasting machine for sandblasting roughening treatment to obtain a pre-treated No. 45 steel with a surface roughness of Ra=7.5. The process parameters are: 1.5mm brown corundum sand is used as abrasive sand, the compressed air pressure is 0.4MPa; the sandblasting distance is 100mm; the sandblasting angle is 75°;

[0186] S2: Set the base layer and metal layer:

[0187] S21: Set the base layer:

[0188] S211: Copper powder, nickel powder, chromium powder and molybdenum powder are weighed in a mass ratio of 85:8:4:3, and mixed evenly to obtain a mixed metal powder; the mixed metal powder and 10 wt % sodium carboxymethyl cellulose-ethanol solution are added into a ball mill in a ratio of 4 g:10 mL, and ball-to-material ratio is 10:1, and ball milling speed is 400 rpm, and the powder is ball-milled to an average particle size of 40 μm to obtain a base layer powder;

[0189] S212: The base layer powder was sprayed on the surface of the pre-treated 45 steel material by supersonic flame spraying technology to obtain a 0.2mm thick base layer; the working parameters of the supersonic flame spraying technology were: oxygen pressure of 1.5MPa, oxygen flow of 1.1L / min, propane pressure of 0.4MPa, propane flow of 100L / min, nitrogen powder feeding pressure of 0.6MPa, and spraying distance of 190mm;

[0190] S22: Set the metal layer:

[0191] S221: Preparation of titanium dioxide @ graphene / carbon nanotube / silicon carbide whisker composite materials: (1) Disperse carboxylated carbon nanotubes in deionized water to obtain a carbon nanotube suspension; disperse silicon carbide whiskers in a 3wt% polyvinyl pyrrolidone aqueous solution to obtain a silicon carbide whisker suspension; disperse graphene oxide in deionized water to obtain a graphene suspension; (2) Under ultrasonic dispersion, slowly add the carbon nanotube suspension to the silicon carbide whisker suspension, ultrasonically treat for 2h, then add the graphene suspension to the mixed system, continue ultrasonically treating for 2h, and finally add ascorbic acid to the mixed system. After ultrasonic treatment for 10min, heat to 95℃ and keep warm for 3h to terminate the reaction. Filter and dry to obtain graphene / carbon nanotube / carbon whisker suspension. (3) under stirring, tetrabutyl titanate, diethanolamine and anhydrous ethanol were slowly added into deionized water (the ratio of the four was 5 g: 1 mL: 20 mL: 20 mL). After the raw materials were completely dissolved, the temperature was raised to 50 °C and stirred for 1.5 h to obtain titanium dioxide sol; (4) the graphene / carbon nanotube / silicon carbide whisker composite material was added into the titanium dioxide sol (the ratio of the two was 1 g: 40 mL), ultrasonically treated for 10 min, and then allowed to stand for 4 h. After filtering, drying and grinding, titanium dioxide@graphene / carbon nanotube / silicon carbide whisker composite material was obtained;

[0192] S222: Weigh the base layer powder and titanium dioxide@graphene / carbon nanotube / silicon carbide whisker composite material in a mass ratio of 95:5, stir and mix them evenly, and then press them into shape at 200 MPa; then place them in a vacuum sintering furnace, heat them to 400°C at a heating rate of 30°C / min, and sinter them for 1.5h; then heat them to 1000°C at a heating rate of 5°C / min, and sinter them for 1h, wait for the furnace to cool, take them out, and complete the sintering;

[0193] S223: adding the sintered product and 10 wt % sodium carboxymethyl cellulose-ethanol solution in a ratio of 4 g:10 mL into a ball mill, and ball milling the mixture to an average particle size of 40 μm at a ball-to-material ratio of 10:1 and a ball milling speed of 400 rpm to obtain a metal layer powder;

[0194] S224: The metal layer powder is sprayed on the surface of the base layer by supersonic flame spraying technology to obtain a 0.5mm thick metal layer, and highly wear-resistant and corrosion-resistant 45 steel is prepared; the working parameters of the supersonic flame spraying technology are: oxygen pressure of 1.5MPa, oxygen flow rate of 1.1L / min, propane pressure of 0.4MPa, propane flow rate of 100L / min, nitrogen powder delivery pressure of 0.6MPa, and spraying distance of 190mm.

[0195] Comparative Example 6: Comparative Example 6 is based on Example 1, with the following modifications: only the enhanced coating is used to paint the 45# steel, specifically:

[0196] A method for preparing highly wear-resistant and corrosion-resistant mechanical steel:

[0197] S1: Pre-processing:

[0198] Cleaning: Use degreased acetone, anhydrous ethanol, and deionized water to ultrasonically clean the surface of No. 45 steel in turn to remove the oil on the surface, complete the cleaning, and dry it for later use;

[0199] S2: Set up paint layer:

[0200] S21: Preparation of enhanced coating: (1) Under nitrogen atmosphere, perfluoropolyether diol and terminal hydroxyl fluorinated polyester polysiloxane are dissolved in an appropriate amount of tetrahydrofuran, and then water-based epoxy resin and dibutyltin dilaurate are added thereto, and then the mixture is heated to 120°C and stirred for 4 hours, and then distilled under reduced pressure and cooled to obtain a modified epoxy resin, wherein the mass ratio of perfluoropolyether diol, terminal hydroxyl fluorinated polyester polysiloxane, water-based epoxy resin and dibutyltin dilaurate is 1:1:8:0.4; (2) 5-amino-2-pyrazinoic acid is dissolved in deionized water, and then a particle size of ≤100 is added thereto. nm carbon black, and then stirring and heating to 75°C for 20 minutes, filtering, washing and drying to obtain modified carbon black, wherein the mass ratio of 5-amino-2-pyrazinoic acid to carbon black is 1:1.2; (3) stirring and mixing the modified epoxy resin, anhydrous ethanol and deionized water, and then adding formic acid to the mixed system to adjust the pH to 5.5, and then adding phytic acid and modified carbon black to the mixed system in turn and stirring and mixing, and finally adding film former BYK-333, anti-aging agent V-480, defoamer XWC-T118 and triethanolamine to the mixed system and stirring and mixing to obtain a reinforced coating;

[0201] The reinforced coating comprises the following components: by weight, 32 parts of modified epoxy resin, 8 parts of modified carbon black, 5 parts of phytic acid, 6 parts of film former BYK-333, 5 parts of anti-aging agent V-480, 3 parts of defoamer XWC-T118, 8 parts of triethanolamine, 25 parts of anhydrous ethanol, and 50 parts of deionized water.

[0202] S22: The reinforcing coating is evenly brushed onto the surface of the No. 45 steel, and dried and cured at 120° C. to obtain a coating layer with a thickness of 4 μm; thus, a highly wear-resistant and corrosion-resistant No. 45 steel is prepared.

[0203] Performance test: The high wear-resistant and corrosion-resistant 45# steels prepared in Examples 1 to 3 and Comparative Examples 1 to 6 and the untreated 45# steels were subjected to relevant performance tests, as follows:

[0204] (1) Adhesion test: According to the standard of GB / T 9286-2021, the adhesion of the coating layer is measured;

[0205] (2) Salt spray resistance test: According to the standard of GB / T 1771-2007, the salt spray resistance of high wear-resistant and corrosion-resistant mechanical steel is measured after being treated in medium salt spray (5%) for 240 hours to evaluate its corrosion resistance;

[0206] (3) Wear resistance test: A friction and wear tester was used to conduct a friction and wear test for 24 hours at a load of 50 N and a rotation speed of 1500 r / min. The wear amount was calculated to evaluate the wear resistance.

[0207] The test results of the above test contents are shown in Table 1:

[0208] Table 1

[0209]

[0210] Result analysis: From the data in Table 1 above, it can be seen that the high wear-resistant and corrosion-resistant mechanical steel prepared by the present invention has excellent corrosion resistance and wear resistance. By comparing Example 1 with Comparative Examples 1 to 2, it can be seen that the titanium dioxide @ graphene / carbon nanotube / silicon carbide whisker composite material has an important influence on the wear resistance of mechanical steel; by comparing Example 1 with Comparative Examples 3 to 6, it can be seen that the coating layer has a small influence on the wear resistance of mechanical steel, but has a very obvious influence on its corrosion resistance; combined with the untreated No. 45 steel, it can be seen that only with the synergistic effect of the metal layer and the coating layer can high wear-resistant and corrosion-resistant mechanical steel with excellent performance be obtained.

[0211] In summary, the present invention prepares a highly wear-resistant and corrosion-resistant mechanical steel with excellent performance.

[0212] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing highly wear-resistant and corrosion-resistant mechanical steel, characterized in that: The following steps are involved: S1: pretreating the surface of the mechanical steel substrate to obtain pretreated mechanical steel; S2: Set the primer layer and metal layer in sequence on the pre-treated mechanical steel surface: S21: The primer powder is sprayed on the surface of the pre-treated mechanical steel by using the supersonic flame spraying technology to obtain the primer; S22: using supersonic flame spraying technology to spray metal layer powder onto the surface of the base layer to obtain a metal layer; S3: evenly brushing the enhanced coating onto the surface of the metal layer, and drying and curing to obtain a coating layer; thus, a highly wear-resistant and corrosion-resistant mechanical steel is prepared; The base layer powder is obtained by mixing and ball milling the following components: 80% to 89% copper powder, 5% to 10% nickel powder, 3% to 5% chromium powder, and 3% to 5% molybdenum powder by mass percentage; the average particle size of the base layer powder is 30 μm to 50 μm; The metal layer powder is obtained by mixing, pressing, sintering and ball milling the following components: 90% to 97% of the base layer powder and 3% to 10% of the titanium dioxide@graphene / carbon nanotube / ceramic whisker composite material by mass percentage; the average particle size of the metal layer powder is 30 μm to 50 μm; The preparation method of the titanium dioxide@graphene / carbon nanotube / ceramic whisker composite material is as follows: (1) dispersing carboxylated carbon nanotubes in deionized water to obtain a carbon nanotube suspension; dispersing ceramic whiskers in a 1wt%~5wt% polyvinyl pyrrolidone aqueous solution to obtain a ceramic whisker suspension; dispersing graphene oxide in deionized water to obtain a graphene suspension; (2) slowly adding the carbon nanotube suspension to the ceramic whisker suspension under ultrasonic dispersion, ultrasonically treating for 1h~3h, then adding the graphene suspension to the mixed system, and continuing the ultrasonic treatment for 1h~3h, and finally adding ascorbic acid to the mixed system, ultrasonically treating for 5min~15min, heating to 90℃~100℃ and keeping warm for 1h~5h, terminating the reaction, filtering and drying to obtain a graphene / carbon nanotube / ceramic whisker composite material; (3) stirring tetrabutyl titanate and diethanol Amine and anhydrous ethanol are slowly added to deionized water. After the raw materials are completely dissolved, the temperature is raised to 45°C~60°C and stirring is continued for 1h~2h to obtain titanium dioxide sol; (4) The graphene / carbon nanotube / ceramic whisker composite material is added to the titanium dioxide sol, ultrasonically treated for 5min~15min, and then allowed to stand for 2h~6h. After filtering, drying and grinding, a titanium dioxide@graphene / carbon nanotube / ceramic whisker composite material is obtained; wherein the mass ratio of carboxylated carbon nanotubes, ceramic whiskers, graphene oxide and ascorbic acid is (0.1~0.2):(0.01~0.05):1:1, wherein the ceramic whiskers include a combination of one or more of silicon carbide whiskers, silicon nitride whiskers and aluminum nitride whiskers; the ratio of tetrabutyl titanate, diethanolamine, anhydrous ethanol and deionized water is 5g:(0.5~2)mL:20mL:20mL; The reinforced coating comprises the following components: by weight, 30 to 35 parts of modified epoxy resin, 6 to 10 parts of modified carbon black, 3 to 8 parts of corrosion inhibitor, 4 to 10 parts of film former, 3 to 8 parts of anti-aging agent, 1 to 4 parts of defoaming agent, 5 to 10 parts of curing agent, 25 to 30 parts of anhydrous ethanol, and 40 to 50 parts of deionized water.

2. The method for preparing a highly wear-resistant and corrosion-resistant mechanical steel according to claim 1, characterized in that: The pretreatment includes two steps of cleaning and sandblasting. The cleaning process is as follows: using degreased acetone, anhydrous ethanol and deionized water to ultrasonically clean the surface of the mechanical steel in sequence to remove the oil stains on the surface, complete the cleaning, and dry it for standby use. The process parameters of sandblasting are as follows: the grinding sand is any one of quartz sand, brown corundum sand and ceramic sand, and its particle size is 0.6mm~2mm; the compressed air pressure is 0.4MPa~0.5MPa; the sandblasting distance is 100mm~120mm; and the sandblasting angle is 72°~78°.

3. The method for preparing a highly wear-resistant and corrosion-resistant mechanical steel according to claim 1, characterized in that: The ceramic whiskers are silicon carbide whiskers, and the ratio of the obtained graphene / carbon nanotube / silicon carbide whisker composite material to the titanium dioxide sol is 1g:40mL.

4. The method for preparing a highly wear-resistant and corrosion-resistant mechanical steel according to claim 1, characterized in that: The preparation method of the enhanced coating is as follows: (1) dissolving perfluoropolyether diol and terminal hydroxyl fluorinated polyester polysiloxane in tetrahydrofuran under a nitrogen atmosphere, then adding water-based epoxy resin and a catalyst thereto, stirring and heating to 100° C. to 150° C. and stirring for reaction for 1 h to 5 h, distilling under reduced pressure and cooling to obtain a modified epoxy resin; (2) dissolving 5-amino-2-pyrazinoic acid in deionized water, then adding carbon black thereto, stirring and heating to 70° C. to 80° C. and stirring for reaction for 10 min to 30 min, filtering, washing and drying to obtain a modified carbon black; (3) stirring and mixing the modified epoxy resin, anhydrous ethanol and deionized water, then adding formic acid to the mixed system to adjust the pH to 5 to 6, continuing to add a corrosion inhibitor and modified carbon black to the mixed system in sequence and stirring and mixing, and finally adding a film former, an anti-aging agent, a defoaming agent and a curing agent to the mixed system and stirring and mixing to obtain an enhanced coating.

5. The method for preparing a highly wear-resistant and corrosion-resistant mechanical steel according to claim 4, characterized in that: The mass ratio of the perfluoropolyether diol, the terminal hydroxyl fluorinated polyester polysiloxane, the water-based epoxy resin and the catalyst is 1:1:(5-10):(0.1-0.6); the catalyst includes any one of dibutyltin dilaurate, stannous octoate, methyltriphenylphosphonium bromide and ethyltriphenylphosphonium bromide; the mass ratio of the 5-amino-2-pyrazinoic acid and the carbon black is 1:(1-1.5); the particle size of the carbon black is ≤100nm.

6. The method for preparing a highly wear-resistant and corrosion-resistant mechanical steel according to claim 1, characterized in that: The process parameters of the supersonic flame spraying technology are: oxygen pressure of 1.5MPa~1.6MPa, oxygen flow rate of 1L / min~1.2L / min, propane pressure of 0.3MPa~0.5MPa, propane flow rate of 100L / min~110L / min, nitrogen powder feeding pressure of 0.5MPa~0.6MPa, and spraying distance of 180mm~200mm.

7. The method for preparing a highly wear-resistant and corrosion-resistant mechanical steel according to claim 1, characterized in that: The pressure used for the compression molding is 150MPa~200MPa; the sintering method is: under vacuum, heating to 350℃~450℃ at a heating rate of 20℃ / min~40℃ / min and sintering for 1h~2h; then heating to 900℃~1100℃ at a heating rate of 5℃ / min~8℃ / min and sintering for 0.5h~1h, waiting for the furnace to cool, taking it out, and completing the sintering; the ball milling method is: adding 8wt%~10wt% of sodium carboxymethyl cellulose-ethanol solution and the raw material to be ball milled into a ball mill, ball milling to the required particle size with the working parameters of ball-to-material ratio (10~15):1 and ball milling speed of 350rpm~450rpm, filtering and drying, and completing the ball milling; wherein, the ratio between the raw material to be ball milled and the sodium carboxymethyl cellulose-ethanol solution is (3g~4g):10mL.

8. The highly wear-resistant and corrosion-resistant mechanical steel prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The highly wear-resistant and corrosion-resistant mechanical steel is obtained by sequentially arranging a primer layer, a metal layer and a coating layer on the surface of a pretreated mechanical steel substrate; the thickness of the primer layer is 0.1 mm to 0.3 mm; the thickness of the metal layer is ≥0.5 mm; and the thickness of the coating layer is 3 μm to 5 μm.

Citation Information

Patent Citations

  • Method for repairing energy-saving corrosion-resistant coating of waste water pump

    CN115449740A

  • Production of roll used for continuous casting improved in heat resistance, corrosion resistance and wear resistance of surface of base material of roll barrel part applied with repeated thermal impact and sliding wear

    JP2000345313A